PRNP genetic variability and molecular typing of natural goat scrapie isolates in a high number of infected flocks - Fragkiadaki, Eirini G (BioMed Central, 2011)
One hundred and four scrapie positive and 77 negative goats from 34 Greek mixed flocks were analysed by prion protein gene sequencing and 17 caprine scrapie isolates from 11 flocks were submitted to molecular isolate typing. For the first time, the protective S146 variant was reported in Greece, while the protective K222 variant was detected in negative but also in five scrapie positive goats from heavily infected flocks. By immunoblotting six isolates, including two goat flockmates carrying the K222 variant, showed molecular features slightly different from all other Greek and Italian isolates co-analysed, possibly suggesting the presence of different scrapie strains in Greece.